Pengembangan Sistem Pengeloaan Bimbingan Belajar Menggunakan Pendekatan Rapid Application Development - Andrian Sah; Sandra Dewi Saraswati; Nofitri Heriyani; Muliati Badaruddin (Journal of Computing and Informatics Research, 2024)
Tutoring plays a crucial role in supporting students' academic achievements by providing additional services outside of school hours. However, the manual management systems still applied by many tutoring centers, such as Bimbingan Belajar Ceria, have caused various issues, including inefficiency and susceptibility to human error. This study aims to develop a web-based Tutoring Management System using the Rapid Application Development (RAD) method. RAD was chosen because it can accelerate the development process through prototyping and iterations that allow adjustments based on user feedback. This is evidenced by the project being completed on time, within approximately 4 months. The system's development results show that the software produced is capable of managing student registration, payments, scheduling, and teacher data. Furthermore, the quality of the software meets expectations, as reflected by the evaluation conducted through usability testing. The test results showed a score of 88%, classified as "Good," indicating that the final product successfully meets user needs